Democracy, Good Governance And Sustainable Development In Nigeria - Nnaa, Biiragbara Godpower; Arugu, Love Obiani (Advances in Social Sciences Research Journal, 2020)
There is the widespread belief amongst scholars and practioners of public administration that good governance and development are the likely outcomes of democracy. However, what is yet to be given much attention is the sustainability of this outcome. This paper entitled, Democracy, Good Governance and Sustainable Development seeks to investigate critically the relationship between democracy, good governance, and sustainable development in Nigeria. In other words, it aims at establishing a nexus between democratization of the political process and the sustainability of its outcomes on the socio-economic and political well-being of the people. The study adopted the descriptive method mainly through the use of secondary data. Using the political economy paradigm as the unit of analysis, the research found out amongst others that democracy as practiced in Nigeria is yet to yield any significant outcome of good governance nor bring about any meaningful development that can be sustained overtime. And this is due to the observed perennial violations of the ethos of democratic practices exhibited by the political class and the dilapidated institutions in the structure of the Nigerian State. It recommends therefore amongst others that emphasis should be laid on democratization of economic opportunities (social democracy), the betterment of the people, and a strong social welfare system. The paper also suggests that it is only through orderly and consistent democratic good governance procedures and practices that gains of development can be sustained.